Sosialisasi Dampak Pemisahan Sampah Organik Dan Non Organik Limbah Rumah Tangga: Desa Sukoanyar, Kecamatan Wajak, Kabupaten Malang, Provinsi Jawa Timur - Dita Rachmawati; Indah Datin Nadliroh (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
Waste has evolved into a substance that is no longer deemed useful. The pace of trash creation rises in lockstep with population growth, posing a rising hazard to the environment. This predicament has been aggravated by the government’s and society’s inadequate treatment of trash. Waste source management has emerged as an option for dealing with the waste problem. A community service program was carried out in the villages of Sukoanyar, Wajak, and Malang to combat the occurrence of garbage. The public’s understanding and awareness of waste issues has improved as a result of material explanations, direct practice, and discussions about how to process and sort household waste. The content that has been explained comprises waste, waste classification based on type, and waste management. It was discovered that the community service program boosted public understanding of waste since more than 65 percent of participants correctly answered the questions. According to the findings of the study, the public’s attitude and conduct regarding trash concerns is positive. It was helped by the existence of garbage disposal facilities supplied by the Village Devices.